Pengaruh Minuman Kunyit Asam terhadap Kejadian Keputihan pada Remaja usia 14-16 tahun di MTs Nurul Muttaqien Tlogowaru Kota Malang - Iwan Abdy; Dewy Indah Lestary (NERSMID : Jurnal Keperawatan dan Kebidanan, 2019)
Leucorrhoea is one problem that has long been a problem for women. Generally women who suffer from vaginal discharge produce too much mucus and cause unpleasant odors. This is caused because of the occurrence of inflammation and infection of the vaginal canal. This study is an analytical study that is maximized in the Quasy Experimental Design. Data analysis in this study uses the Chi Square Test because both variables use nominal data scales. The data collection tool used in this preliminary study was a questionnaire. The results showed that after being given turmeric acid as much as 200 ml every day for 7 consecutive days, the incidence of vaginal discharge in adolescents aged 14-16 years in MTS Nurul Muttaqien Tlogowaru Malang City decreased to 17 people (36.2%) the incidence of leucorrhoea is because this turmeric acid drink contains curcumin which acts as an anti-bacterial, anti-inflammatory, anti-oxidant. Based on the results of the analysis and discussion in this study it can be concluded that turmeric acid drink given to adolescents aged 14-16 years for 7 consecutive days can provide an alternative to overcome physiological vaginal discharge. Suggestions for further research are expected to increase the contribution of knowledge, especially teenagers about overcoming physiological vaginal discharge one of them by consuming turmeric acid drink.